Analysis of Surface Water Availability to Meet Agricultural Water Demands in Kediri Regency, Indonesia (ASEAN Journal on Science and Technology for Development, 2022)
This study aims to analyze the potential of surface water to meet agricultural water needs in Kediri Regency, Indonesia. Data from government agencies (i.e., Indonesian Bureau of Meteorology, Climatology, and Geophysics and Kediri Agriculture Office) and fieldwork were analyzed to achieve the research objectives. The data obtained consisted of rainfall, temperature, infiltration capacity, soil texture, root depth, and agricultural land area. The potential of surface water resources was calculated by using the Thornthwaite–Mather water balance method. The water balance results were compared with agricultural water demands, which were calculated on the basis of the area of agricultural land and type of crop, particularly paddy fields. Critical and noncritical conditions for surface water resources were classified on the basis of the ratio between the availability of surface water resources and the demand for agricultural water. Results showed that the total surface water potential widely varied by season. The water balance calculation indicated that all subwatersheds (SWs) experienced a water surplus in the rainy season, whereas almost all SWs were deficient in surface water in the dry season, Overall, the surface water in Kediri was critical in the rainy season and more severely critical in the dry season. The results of this study indicated that the high demand for agricultural water can affect the availability of water resources in the tropics. The results are expected to be considered in determining regional planning related to the use and need of water resources and supporting infrastructures.